2021
DOI: 10.25081/jp.2021.v13.6560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed invigoration with inorganic nanoparticles on seed yield in chilli (Capsicum annum)

Abstract: An experiment was conducted to study the effect of seed invigoration with inorganic nanoparticles on plant growth and seed yield of chilli. Seed invigoration with nano particles of ZnO and TiO2 was found to be beneficial in improving yield and yield attributes. Seed treatment with nano ZnO @ 1300 mg kg-1 of seed and nano TiO2 @ 900 mg kg-1 exhibited increased plant height, fruits per plant, fruit length, fruit yield, number of seeds per fruit and seed yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The variation in fruit plant have been to sex ratio and fruit set percentage. The results are in agreement with the finding of Mathew et al, [19].…”
Section: Yield and Quality Parametersupporting
confidence: 94%
“…The variation in fruit plant have been to sex ratio and fruit set percentage. The results are in agreement with the finding of Mathew et al, [19].…”
Section: Yield and Quality Parametersupporting
confidence: 94%
“…In certain situations, seed growers distribute outdated seeds to farmers, who then store the expired seeds for their own use. As a result, seed invigoration via seed treatment is an important strategy for improving seed performance, resulting in a faster germination rate and a higher percentage of germinated seeds [2].…”
Section: Introductionmentioning
confidence: 99%
“…Plant species differs physiologically so their uptake of nanoparticles and the effects of different concentration of nanoparticle on them may differs from plant to plant. Researchers have found that nanoparticle seed treatment could improve the seedling character (Singh et al, 2012), induce growth and development of plants (Khater, 2014), increase the yield potential (Mathew et al, 2021) and improve the storage life of seeds (Das and Dutta. 2022).…”
Section: Introductionmentioning
confidence: 99%